Insectivorous bat assemblages in relation to spatial aspects of virgin jungle reserves in Peninsular Malaysia / Joann Christine Luruthusamy - Luruthusamy, Joann Christine (2010)
The tropical region supports the highest diversity of bat fauna known. Reasons for their success are mainly due to their large geographical ranges, the diversity of habitats, various foraging strategies and the tendency to exhibit a variety of roosting behaviour. This study addresses the issue of insectivorous bat distribution in relation to spatial aspects such as geography, size, distance and topography. This information was gathered from the 958 individuals and 27 insectivorous bat species that were captured and identified over a span of 18 months. This study which included six virgin jungle reserves of various sizes across Peninsular Malaysia revealed that the Peninsular is dominated mainly by the Hipposiderids and Rhinolophids family and that bat species composition is driven by elevational range and forest surroundings, and not by geography. As for the effect of primary habitat size, this study showed that VJR size did not show any correlation with insectivorous bat assemblages. The impact of VJR size class on its surrounding logged over forest indicated that the population of bats 200 m away from the VJR tend to increase with increasing VJR size but the proportion of bats furthest away from the VJR (> 600 m) decreased. Although topography did not have an effect on bat distribution within each site, bat abundance and species richness were the highest at the valley. Despite the various aspects of a forest (topography, size, distance, etc.), there is no one single reason behind bat species distribution, but an interaction of a few factors. Different species tend to be most abundant around their environmental optimum. Therefore conservation strategies should focus on determining a balance forest structure for the survival of each bat species.